2018
DOI: 10.24841/fa.v26i2.329
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación Del Barcoding Al Manejo Y Conservación De Peces Y Sus Subproductos en La Amazonía Peruana

Abstract: Fue generado y depositado en el GenBank secuencias nucleotidicas del gen COI de 207 especies de peces comercializados en los mercados de consumo y ornamental en la Amazonia peruana. Posteriormente este banco de secuencias nucleotídicas fueron utilizadas como base de comparación en la identificación específica exitosa de: i) larvas de bagres colectadas en tres cuencas hidrológicas (Ucayali, Napo y Marañón), mostrando ser una alternativa mucho más segura que las determinaciones mediante análisis morfológico o mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The Peruvian Amazon basin has a wide diversity of fish. Among them, the boquichico (Prochilodus nigricans) is one of the most consumed species as it is part of the local population's regular diet, being a good source of proteins and vitamins, among other nutrients [8]. It is mainly sold fresh and generally whole since it has many thorns.…”
Section: Introductionmentioning
confidence: 99%
“…The Peruvian Amazon basin has a wide diversity of fish. Among them, the boquichico (Prochilodus nigricans) is one of the most consumed species as it is part of the local population's regular diet, being a good source of proteins and vitamins, among other nutrients [8]. It is mainly sold fresh and generally whole since it has many thorns.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many have turned to the assistance of community scientists to aid in catch effort and identification of individual landings, yet accurate species identification remains a challenge (Gardiner et al, 2012 ; Swanson et al, 2016 ). Genetic approaches have also been implemented to identify many of the fish species inhabiting the Amazon (de Santana et al, 2021 ; García‐Dávila et al, 2017 ), but these approaches also rely on well‐identified and vouchered genetic libraries that are still missing for Amazonian fishes. These techniques require expensive storage and sample processing technology, which are not readily available in most institutions within the Amazon (de Santana et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%